2021
DOI: 10.3390/ijms22105357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fatty Acids in Ceramide Pathways and Their Influence on Hypothalamic Regulation of Energy Balance: A Systematic Review

Abstract: Obesity is a global health issue for which no major effective treatments have been well established. High-fat diet consumption is closely related to the development of obesity because it negatively modulates the hypothalamic control of food intake due to metaflammation and lipotoxicity. The use of animal models, such as rodents, in conjunction with in vitro models of hypothalamic cells, can enhance the understanding of hypothalamic functions related to the control of energy balance, thereby providing knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 120 publications
(207 reference statements)
0
11
0
Order By: Relevance
“… 39 Overaccumulation of FFAs could induce excessive ceramide levels, 40 which were reported to ultimately cause mitochondrial dysfunction and lipotoxicity. 41 , 42 In this study, we found that HFD-induced obesity led to mitochondrial damage; as the number of mitochondria decreased, they became swollen, and the cristae ruptured.…”
Section: Discussionmentioning
confidence: 52%
“… 39 Overaccumulation of FFAs could induce excessive ceramide levels, 40 which were reported to ultimately cause mitochondrial dysfunction and lipotoxicity. 41 , 42 In this study, we found that HFD-induced obesity led to mitochondrial damage; as the number of mitochondria decreased, they became swollen, and the cristae ruptured.…”
Section: Discussionmentioning
confidence: 52%
“…Palmitate is one of the most important components of an HFD. It is also the predominant fatty acid consumed by humans [48][49][50]. Here, we showed that palmitate injected directly into the hypothalamus of mice promoted the increased activation of CREB, which predominantly occurred in Pomc neurons.…”
Section: Discussionmentioning
confidence: 61%
“…As most ceramides appear to be synthesized de novo, diet appears to be a major contributor to ceramide composition and the level of circulating ceramides in humans [ 174 ]. Fatty acids from the diet are expected to be reflected in the ceramide composition [ 175 , 176 ].…”
Section: Dietary Interventions As Anti-ceramide Treatmentsmentioning
confidence: 99%